Characteristics of aluminosilicates prepared from rice husk silica and aluminum metal - Simanjuntak, W.; Sembiring, S.; Manurung, P.; Situmeang, R.; Low, It Meng (Elsevier Science Ltd, 2013)
This study investigated use of the electrochemical method to prepare aluminosilicates from rice husk silica and aluminum metal. The aluminosilicate precursors were characterized using Scanning Electron Microscopy/Energy Dispersive X-ray spectroscopy (SEM/EDX), Fourier Transform Infrared (FTIR) spectroscopy, and X-ray Diffraction spectroscopy (XRD). The precursors were subsequently sintered at 700–1400 °C and their microstructures and phase compositions were characterized. Results showed that the proposed method could be used to prepare aluminosilicates with high uniformity in terms of surface morphology and the particle size with mullite and quartz as the major phases formed.